Excel data analysis : your visual blueprint for analyzing data, charts, and Pivot Tables - McFedries, Paul. (Indianapolis, IN : Wiley, 2013)
Provides instructions on using Excel to analyze data, covering such topics as creating formulas, using financial functions, organizing worksheet data, working with PivotTables, and automating with macros.
Rev. ed. of: Excel data analysis : your visual blueprint for creating and analyzing data, charts and PivotTables / by Denise Etheridge. 3rd ed. c2010.
"Visual, a Wiley brand."
Includes index.
Keywords: Microsoft Excel (Computer file).; Business -- Computer programs; Electronic spreadsheet